Evaluation of E?ect of Bolus Doses of Oxytocin in Caesarean Section Under Spinal Anaesthesia - Md Nishat Akhtar; Shazia Ahmad; Ikram Ilahi (Academia Anesthesiologica International, 2020)
Background: The aim is to compare effect of bolus doses of oxytocin in caesarean section under spinal anaesthesia. Subjects and Methods: A total of seventy- eight women were included. Patients in group I received one unit of bolus oxytocin and in group II received two units of bolus oxytocin. The subject was given a spinal block with 2 mL of 0.5% bupivacaine. The uterine tone was assessed in both groups. Intraoperative blood loss, heart rate, uterine tone and possible side effects were also compared. Results: Mean age was 26.5 years in group I and 24.8 years in group II, gestational age was 38.4 weeks in group I and 38.7 weeks in group II, height was 156.7 cms in group I and 156.2 cms in group II and weight was 68.9 kgs in group I and 70.1 kgs in group II. Uterine tone was adequate in 30 (76.9%) in group A and 35 (89.7%) in group B. Blood loss was 1038.2 mL in group A and 740.6 mL in group B. Conclusion: One unit of oxytocin was inadequate for adequate uterine contraction as compared to two doses of oxytocin where uterine contraction rate was high. Blood loss was also lowered in group B where two units of oxytocin was administered.